Increasing physical activity in a secure psychiatric service for women. Issue 3 (14th September 2015) - Long, Clive; West, Rachel; Rigg, Samantha; Spickett, Rebecca; Murray, Lynne; Savage, Paul; Butler, Sarah; Stillman, Swee-Kit; Dolley, Olga
Abstract : Purpose: – The purpose of this paper is to evaluate the effectiveness of measures designed to increase physical activity in women in secure psychiatric care. Design/methodology/approach: – A range of interventions (environmental and motivational) designed to increase participation in physical activities were introduced on two secure wards for women. A pre-post design assessed frequency, duration and intensity of physical activity, attendance at physical activity sessions, exercise motivation, exercise-related mood, attitudes to exercise and health and biological indices. Measures collected over a three-month baseline period were repeated six months post-intervention. Findings: – Significant changes occurred in both attitudes to exercise and health, exercise motivation and exercise behaviour following change initiatives. With the exception of resting pulse rate and perceived exertion, the increased level of activity was not reflected in changes in body mass index, body fat or body muscle. Practical implications: – Management led, multi-disciplinary interventions to increase physical activity can have a positive impact on both lifestyle behaviours and physical health. Originality/value: – This study adds to a small literature on increasing physical activity in women in secure psychiatric settings where obstacles to change are formidable.